Development of Electronic Module Using Creative Problem-Solving Model Equipped with HOTS Problems on The Kinetic Theory of Gases Material - I Made Astra; Raihanati Raihanati; Nur Mujayanah (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
This research aims to develop and produce an e-module of physics using a creative problem-solving model equipped with HOTS problems on the kinetic theory of gases material as independent teaching material for high school students of class XI IPA. The research method used in this study is the Research and Development (R & D) method using the model of Dick & Carey. The creative problem-solving model has six learning stages. The electronic module is equipped with HOTS questions, where HOTS is a high- level thinking skill that includes three indicators, including analyzing skills (C4), evaluating (C5), and creating (C6). The instrument used in this study is a questionnaire using a Likert scale. This e-module has gone through a validation test involving material experts, media experts, and learning experts. The results of expert validation are 82.83%. The result in the field-test by physics teachers shows an average score of 83.05%. The field-test results by the students of SMAN 16 Jakarta shows an average score of 93.44%. The result of the effectiveness test had a gain score of 0.502 indicates that the e-module can increase students’ high order thinking skills in the middle classification. These results show that the e-module of physics using a creative problem-solving model equipped with HOTS questions in the kinetic theory of gases material can be feasible as independent teaching material and can increase students’ high order thinking skills.